Morphological changes of mitochondria-related to apoptosis during postmortem aging of beef muscles - Chunmei Liu; Zhenjiang Ding; Zihan Zhang; Laiyu Zhao; Chunhui Zhang; Feng Huang (Food Chemistry: X, 2023)
This study aimed to investigate how postmortem muscle cells' mitochondria changed in morphology from three aspects: the outer membrane, cristae, and fission/fusion. Atomic force microscopy (AFM) results showed that mitochondria underwent a morphology transformation from normal to swelling and collapse. Meanwhile, the cleavage of OPA1, upregulation of OMA1, downregulation of Mic60 and transmission electron microscope micrographs revealed that mitochondrial cristae ruptured with an aging time extended. Additionally, the increased expressions of Fis1 and Drp1, and the AFM topographic images mutually confirmed mitochondrial fission. These results further proved from the perspective of mitochondrial morphology that the degree of mitochondrial damage increased with the postmortem aging time extended, which was consistent with the results of the release of cytochrome c caused by the increase of mitochondrial permeability transition pore opening and the decrease of mitochondrial membrane permeability, and further induced the apoptosis of postmortem muscle cells.